2019
DOI: 10.3233/xst-190568
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of Monte Carlo model of Siemens Oncor® linear accelerator for 18MV photon beam: Determination of initial electron beam parameters

Abstract: OBJECTIVE: This study aims to benchmark a Monte Carlo (MC) model of the 18 MV photon beam produced by the Siemens Oncor® linac using the BEAMnrc and DOSXYZnrc codes. METHODS: By matching the percentage depth doses and beam profiles calculated by MC simulations with measurements, the initial electron beam parameters including electron energy, full width at half maximum (spatial FWHM), and mean angular spread were derived for the 10×10 cm2 and 20×20 cm2 field sizes. The MC model of the 18 MV photon beam was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Analytical dose calculation algorithms suffer from a clinically significant disagreement with measurement when treatment planning involves inhomogeneous areas. [ 1 ] These errors can become a dominant source of inaccuracy in treatment planning, especially in precision dose delivery techniques. Considering the uncertainties of dosimetry and treatment plan delivery, the importance of accurate dose calculations is highlighted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical dose calculation algorithms suffer from a clinically significant disagreement with measurement when treatment planning involves inhomogeneous areas. [ 1 ] These errors can become a dominant source of inaccuracy in treatment planning, especially in precision dose delivery techniques. Considering the uncertainties of dosimetry and treatment plan delivery, the importance of accurate dose calculations is highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…However, the benchmarking process can become more targeted using sensitivity analysis of the calculated absorbed dose distributions to different parameters of linac and electron beam properties. [ 1 4 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…ese steps are ultimately designed to obtain the signi cant parameters in TPS model building. Many investigations have been conducted to benchmark the incident electrons of other medical linear accelerators such as Elekta [3][4][5], Varian [6][7][8][9], and Siemens [10,11], but no dosimetric studies on the XHA600D accelerator have yet been found. And unlike these references, this study speci cally analyzed the e ects of these four incident electron parameters on PDDs and OARs in di erent beam elds and the details of the benchmarking process to obtain accurate incident electron information of the XHA600D accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…proposing various experimental setups and methods of such analysis [6][7][8][9][11][12][13][14][15][16][17][18]. In the study of Almberg et al [9] an algorithm is proposed to determine values of two parameters (nominal energy and spot size) of the primary electron beam model, basing on depth and lateral photon beam profiles measured for three fields: 2x2, 10x10, and 20x20 cm2.…”
Section: Introductionmentioning
confidence: 99%
“…The last two steps require an extensive MC simulation effort while being based on a trial-and-error approach. Other studies of [13][14][15][16][17][18] are also based on a trial-and-error approach which, while being computationally demanding, offers no systematic procedure for estimating parameter values in the applied model of the primary electron beam.…”
Section: Introductionmentioning
confidence: 99%